Control of Magnetopause Flux Rope Topology by Non-local Reconnection - Mejnertsen, Lars; Eastwood, Jonathan P.; Chittenden, Jeremy P. (Frontiers in Astronomy and Space Sciences, 2021)
Dayside magnetic reconnection between the interplanetary magnetic field and the Earth’s magnetic field is the primary mechanism enabling mass and energy entry into the magnetosphere. During favorable solar wind conditions, multiple reconnection X-lines can form on the dayside magnetopause, potentially forming flux ropes. These flux ropes move tailward, but their evolution and fate in the tail is not fully understood. Whilst flux ropes may constitute a class of flux transfer events, the extent to which they add flux to the tail depends on their topology, which can only be measured in situ by satellites providing local observations. Global simulations allow the entire magnetospheric system to be captured at an instant in time, and thus reveal the interconnection between different plasma regions and dynamics on large scales. Using the Gorgon MHD code, we analyze the formation and evolution of flux ropes on the dayside magnetopause during a simulation of a real solar wind event. With a relatively strong solar wind dynamic pressure and southward IMF, the dayside region becomes very dynamic with evidence of multiple reconnection events. The resulting flux ropes transit around the flank of the magnetosphere before eventually dissipating due to non-local reconnection. This shows that non-local effects may be important in controlling the topology of flux ropes and is a complicating factor in attempts to establish the overall contribution that flux ropes make in the general circulation of magnetic flux through the magnetosphere.